RATIO ANALYSIS AND MANAGEMENT DECISION-MAKING OF LIST DEPOSIT MONEY BANKS IN NIGERIA (Journal of Global Accounting, 2026)
This study evaluated the effect of ratio analysis on management decision making of listed deposit money banks in Nigeria. In specific terms, the study assessed how current ratio, cash ratio, debt to equity ratio, and debt to asset ratio influenced return on investment. Ex post facto research design was adopted for the study which population was thirteen (13) listed deposit money banks in Nigeria. A total of eleven banks (11) was however purposively sampled. Secondary data were obtained from audited annual financial statements for the periods 2012 - 2024, were subjected further analysis using panel regression analysis technique for the test of the relevant hypotheses, after Hausman specification test. The findings revealed that: current ratio had a negative and significant effect on the management decision making of listed deposit money banks in Nigeria (b = -0.010939, p-value = 0.0000); cash ratio had a positive but insignificant effect on the management decision making of listed deposit money banks in Nigeria (b = 0.000280, p-value = 0.6625); debt to equity ratio had a negative and significant effect on the management decision making of listed deposit money banks in Nigeria (b = -0.000276, p-value = 0.0004); debt to asset ratio had a positive and significant effect on the management decision making of listed deposit money banks in Nigeria (b = 0.219299, p-value = 0.0000). It was concluded that ratio analysis significantly influences management decision making in deposit money banks in Nigeria. The study therefore recommended that bank managers in listed deposit money banks in Nigeria should maintain an optimal level of liquidity rather than holding excessive current assets, ensuring that available funds are actively deployed into profitable lending and investment opportunities to improve returns and strengthen decision outcomes.
Keywords: Cash Ratio; Current Ratio; Deposit Money Banks; Management Decision Making; Ratio Analysis